AN ANALYSIS OF PRONUNCIATION ON THE ENGLISH WORDS HAVING VOWELS AND DIPHTHONGS AT UNIVERSITY OF MUHAMMADIYAH TANGERANG - Ella - Agustin; Moh. Iqbal Firdaus; Eka Ugi Sutikno (Globish: An English-Indonesian Journal for English, Education, and Culture, 2023)
This research aims to analyze the sixth semester students’ pronunciation at University of Muhammadiyah Tangerang in Academic Year 2021/ 2022 in relation to English words which having vowels and diphthongs. This research is a kind of a qualitative research which designed through several stages, they are; the process of data collection, analyzing the gaining data, and interpreting the gaining data that has been analyzed. This research has selected 30 students to take part as respondents in this research. Simple random sampling has been used to select those 30 respondents who take part in this research. The results show that, there have been several issues which may be obstacles to students’ pronunciation, especially to English words which having vowels and diphthongs sounds, they are: the effect of the first language, lack of awareness in phonemic symbols, miss-hearing the pronunciation features, and neurobiology of affective. However, in accordance with the issues related to students’ pronunciation, there have been found several solution which may be value to overcome those issues mentioned, they are; creating own habit in English during daily communications, increasing awareness in phonemic symbols, increasing the level of activities in relation to listening which may be value to encourage awareness in hearing various pronunciation features. Keywords: Pronunciation, Vowels, and Diphthongs